Islam and the Rise of Islamic States in Sub-Saharan Africa - Touray, Ensa (Journal of Philosophy, Culture and Religion, 2023)
Purpose: This paper highlights the contribution of trans-Saharan trade as a major medieval trading system which created vibrant commercial link between the people of West and North Africa. It further examines the mode of penetration of Islam into West Africa and the rise of Islamic movements. It demonstrates the significance and the consequence of change depicted by the rise of European capitalist expansion which incorporated the entire West Africa into the capitalist Atlantic maritime trading system in the 16th to 18th centuries. It finally reveals the role of medieval trans-Saharan and the Atlantic maritime trade in catalyzing Muslim uprising and the creation of the theocratic states of Bundu, Futa Toro in the Senegalese Middle valley, and Futa Imamate in Futa Jalon in Guinea Conakry. Methodology: The study employed both primary and secondary sources of data collection. The primary data which comprised Oral interviews which were conducted with 18 selected elderly local historians in West Africa. The oral interviews were obtained with tape recorders, which contained traditional Mandinka and Fula versions of the history of Futa and wars in West Africa. Some interviews which were recorded in 2012 during the research conducted by the University of The Gambia's Socio-Historical Fact Finders in the Republic of Guinea were also used. Findings: The study found out that West as a regional entity evolved in a broader historical context as a result of the influence from Medieval Western Sudanic Empires symbolized by the establishment of trans-Saharan Trade until the modern period that marked the rise of the influence from Atlantic system symbolized by the arrival European capitalist nations.